THE INFLUENCE OF ORGANIZATIONAL CULTURE, SELF-EFFICACY, WORK MOTIVATION AND JOB SATISFACTION ON THE PERFORMANCE OF UMN AL-WASHLIYAH LECTURERS IN MEDAN - Samsul Bahri; Benyamin Situmorang; Edidon Hutasuhut (Jurnal Ilmiah Teunuleh, 2020)
This study aims to answer several hypotheses about the direct influence of organizational culture, self-efficacy, work motivation, and job satisfaction on work motivation, job satisfaction, and lecturer performance. The research technique used proportional random sampling to a sample of 152 of 246 lecturers UMN Al-Washliyah Medan, with research instruments using questionnaires with the scale Likert. Then the data is processed and analyzed with path analysis, thus producing an analysis with a coefficient of path 0.30 on the direct influence of organizational culture on work motivation, path coefficient 0.43 on the direct influence of self-efficacy on work motivation, path coefficient 0.47 on the direct influence of organizational culture on job satisfaction, coefficient of path 0.28 on the direct influence of self-efficacy on job satisfaction, path coefficient 0.22 on the direct influence of organizational culture on performance, the coefficient of line 0.15 on the direct influence of self-efficacy on lecturer performance, the coefficient of line 0.23 on the direct influence of work motivation on lecturer performance, and the coefficient of path 0.28 on the direct influence of job satisfaction on lecturer performance. From the results of the analysis, to improve the performance of lecturers need to be made various efforts, among others, by improving organizational culture, self-efficacy, work motivation, and job satisfaction.